Austerity policies, 'precarity' and the nonprofit workforce: A comparative study of UK and Canada. (September 2016) - Cunningham, Ian; Baines, Donna; Shields, John; Lewchuk, Wayne
Drawing on qualitative interview data from case studies in Scotland and Canada in the post 2008 era, this article explores the impact of austerity policies on the conditions and experience of employment in two nonprofit social service agencies and their shifting labour process. Despite differences in context, the article finds a similarity of experience of austerity-compelled precarity at several levels in the agency. This precarity increased management control and evoked little resistance from employees. These findings contribute to our understanding of austerity as articulated differently in different contexts, but experienced similarly at the front lines of care work.